ByzRev 07.2025.002: Cornelia A. Tsakiridou, The Orthodox Icon and Postmodern Art:: Critical Reflections on the Christian Image and Its Theology (Routledge Research in Art and Religion). New York – London: Routledge 2025. - Constas, Maximos (The Byzantine Review, 2025)
Cornelia A. Tsakiridou, The Orthodox Icon and Postmodern Art: Critical Reflections on the Christian Image and Its Theology (Routledge Research in Art and Religion). New York – London: Routledge 2025. 190 pp., 39 figs. – ISBN 978-1-032-18113-4